Late Quaternary stratigraphy, chronology, and depositional processes on the slope of S.E. Baffin Island, detrital carbonate and Heinrich events: Implications for onshore glacial history - Andrews, John; Kirby, M.; Jennings, Anne; Barber, D. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1998)
AbstractIn order to describe ice sheet/ocean interactions at the NE margin of the Laurentide Ice Sheet over 40 radiocarbon dates have been obtained on foraminifera from nine, 2.5 to 11 m piston cores from the slope of SE Baffin Island. The cores were collected off Cumberland Sound and north of Hudson Straitfrom 750 to 1 510 m waterdepth. Rates of sediment accumulation varied between 20 and 40 cm/ky. Six cores contain high-resolution records of events during Marine Isotope Stage (MIS) 2 and parts of 1 and 3, whereas three cores have core top dates of ≥30 ka and thus provide information on MIS 3 and possibly 4/5. The cores include three main facies: Lithofacies A - yellowish/buff detrital carbonate-rich sediment, also referred to as Detrital Carbonate (DC-) events; Lithofacies B - olive-green detrital carbonate-poor sediment; and Lithofacies C - a black sedimentary unit. The lithofacies represent changes in glacial sources, ice sheet proximity, and processes of deposition. We conclude that there are DC- events correlative with Heinrich events H-1, H- 2, and H-4 in the North Atlantic; however, we find no compelling evidence for a DC-layer during H-3 (ca. 27 ± ka). There are three to four distinct DC- events after H-4 (ca.35 ± ka) but their exact ages are difficult to determine. Grain-size spectra and X-radiographs show that the DC-sediments are stratified to massive silty-clays with little sand, but generally have higher sand percentages at the base. DC-layers were deposited in part from turbidity currents, melting of icebergs, and rain-out of fine-grained silts and clays. In contrast, ice distal sediments in the eastern North Atlantic recorded H-events as an abrupt increase in ice rafted sand-size particles. In our study area, H-layer thicknesses vary from 0 and 70 cm for H-1 and 20 to 90 cm for H-2; H-4 is ≥60 to 100 cm thick. Over the total length of our records, the sedimentary conditions have been dominated by hemipelagic deposition (lithofacies B), implying that those times when ice reached the shelf (lithofacies A and C) have been short.